2019
DOI: 10.1055/s-0039-1694768
|View full text |Cite
|
Sign up to set email alerts
|

Six-Dose Intravenous Tranexamic Acid Regimen Further Inhibits Postoperative Fibrinolysis and Reduces Hidden Blood Loss following Total Knee Arthroplasty

Abstract: There is no consensus regarding the ideal dosages and times of multiple-dose intravenous tranexamic acid (IV-TXA) administration in total knee arthroplasty (TKA). This study aimed to assess the effect of six-dose IV-TXA with the total dosage more than 6 g on postoperative fibrinolysis and hidden blood loss (HBL) after primary TKA. A total of 175 patients were randomized into three groups to receive placebo (group A), or a single preoperative dose of 20 mg/kg IV-TXA (group B), or six-dose IV-TXA from the beginn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 22 publications
1
34
0
Order By: Relevance
“…Lei et al [58] reach the same conclusion by comparing 20 mg/kg and 60 mg/kg TXA intravenously. Moreover, Zhang et al [52] even reported a better outcome of six-dose IV TXA. Besides, Tammachote et al [59] compared high dosage (3 g) with low dosage (0.5 g) for IA TXA and also found a better outcome of high dosage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lei et al [58] reach the same conclusion by comparing 20 mg/kg and 60 mg/kg TXA intravenously. Moreover, Zhang et al [52] even reported a better outcome of six-dose IV TXA. Besides, Tammachote et al [59] compared high dosage (3 g) with low dosage (0.5 g) for IA TXA and also found a better outcome of high dosage.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, the DVT rate might be influenced by the inclusion criteria, and the RCT of TXA in a DVT high-risk population might be required to validate our findings. Furthermore, repeated dose seemed a better choice than a single dose in both IV and IA administration [52,[57][58][59], and therefore, different methods of administration may influence the result. Lastly, data for Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The most common IV TXA dose appears to be approximately 10 to 20 mg/kg, which has been shown to maintain the minimum therapeutic level for approximately 3 hours. [ 36 , 37 ] The oral dose usually ranged from 1 g to 4 g, and the time to the administration of TXA ranged from 1 hour to 8 hours before surgery. [ 37 ] The most common oral TXA dose was 2 g, and the time to administration was 2 hours before surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The safety of multiple doses of TXA in OA patients undergo TKA has been con rmed by some studies. [15,31,32] To our acknowledge, this study was the rst study to observe the clinical effect of multi-dose TXA after TKA in patients with RA. We used 3 doses of IV-TXA (1 g) after surgery, the anti brinolytic effect was maintained in the whole process of brinolysis, the HBL, the drop in Hct and Hb during hospitalization was lower than that of single dose.…”
Section: Discussionmentioning
confidence: 99%